2001
DOI: 10.1126/science.1062693
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Structure of Ionized Helium in the Intergalactic Medium with the Far Ultraviolet Spectroscopic Explorer

Abstract: The neutral hydrogen (H I) and ionized helium (He II) absorption in the spectra of quasars are unique probes of structure in the early universe. We present Far-Ultraviolet Spectroscopic Explorer observations of the line of sight to the quasar HE2347-4342 in the 1000 to 1187 angstrom band at a resolving power of 15,000. We resolve the He II Lyman alpha (Lyalpha) absorption as a discrete forest of absorption lines in the redshift range 2.3 to 2.7. About 50 percent of these features have H I counterparts with col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
178
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(190 citation statements)
references
References 31 publications
9
178
3
Order By: Relevance
“…It is unclear whether the H I and He II reionization epochs were coeval ; it is certainly possible with a sufficiently hard ionizing source spectrum, from, e.g., quasars or zero-metallicity stars (Giroux & Shapiro 1996 ;Tumlinson & Shull 2000). The present data, however, indicate that He II reionization occurred at z D 3 (Jakobsen et al 1994 ;Hogan, Anderson, & Rugers 1997 ;Reimers et al 1997 ;Kriss et al 2001), and that of hydrogen before z D 6. The degree to which QSOs inÑuence the process of reionization depends on their relative abundance at high redshifts.…”
Section: Introductioncontrasting
confidence: 44%
“…It is unclear whether the H I and He II reionization epochs were coeval ; it is certainly possible with a sufficiently hard ionizing source spectrum, from, e.g., quasars or zero-metallicity stars (Giroux & Shapiro 1996 ;Tumlinson & Shull 2000). The present data, however, indicate that He II reionization occurred at z D 3 (Jakobsen et al 1994 ;Hogan, Anderson, & Rugers 1997 ;Reimers et al 1997 ;Kriss et al 2001), and that of hydrogen before z D 6. The degree to which QSOs inÑuence the process of reionization depends on their relative abundance at high redshifts.…”
Section: Introductioncontrasting
confidence: 44%
“…Recent work on the first stars has focused on signatures such as the effects of stellar radiation and nucleosynthesis on their host galaxies and the IGM (Gnedin & Ostriker 1997;Haiman & Loeb 1997;Ferrara, Pettini, & Shchekinov 2000;Abia et al 2001;Ricotti, Gnedin, & Shull 2002)-loosely grouped under stellar and supernova (SN) feedback-and the potential presence of large numbers of stellar remnants in galactic halos in baryonic dark matter scenarios (Fields, Freese, & Graff 1998). These studies have been directly motivated by observations of the reionization (Becker et al 2001;Kriss et al 2001) and trace metal enrichment (Songaila 2001) of the high-z IGM and the detection of solar-mass dark objects in our Galactic halo by microlensing experiments (Alcock et al 2000). Although it is unclear if the same population of early stars can be tied unambiguously to all of these data, it is likely that they contributed significantly to the ionizing photon budget and metal production at early times.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic studies of high-z quasars and galaxies blueward of their rest-frame H i and He ii Ly emission have revealed that He ii reionization occurs at z $ 3 (Kriss et al 2001) and that of H i before z $ 6 (Becker et al 2001). Such spectroscopic observations, along with increasingly precise data on the cosmic microwave background (CMB), are beginning to place strong complementary bounds on the redshift of H i reionization z reion;H .…”
Section: Introductionmentioning
confidence: 99%
“…Since its first detection at z ¼ 3:3 (Jakobsen et al 1994), such a feature has been progressively found in quasar spectra at higher redshifts: z ¼ 3:5 (Zheng et al 2004a) and z ¼ 3:8 (Zheng et al 2005). Measurements of the intergalactic helium and hydrogen Ly opacities show He ii was ionized to He iii before z ' 2:8 (Reimers et al 1997;Kriss et al 2001), while intergalactic hydrogen was ionized before z ' 6 (Fan et al 2002). Theoretical models (Haardt & Madau 1996;Madau et al 1999;Barkana & Loeb 2002;Wyithe & Loeb 2003;Cen 2003) suggest that the reionization of the IGM proceeds in several stages, evolving from cosmic ''bubbles'' in the vicinity of local ionizing sources that eventually fill all of intergalactic space.…”
Section: Introductionmentioning
confidence: 99%